Diseño de un sistema de bombeo de agua Glicolada para enfriadores de cavas de maduración usando refrigerante natural R-744 (CO2) (2022)
In this work, it is proposed to carry out a design consisting of a glycol pumping station that works in cascade with a natural refrigerant such as CO₂, taking into account a smaller space ratio than the existing pumping station, which has been in operation for about 25 years. Service and operates by pumping glycol in cascade with R717 ammonia. The design incorporates several requests from the requesting company, such as working with a new refrigerant in the industry such as R744 (CO₂), and that the pumping station be adaptable to the demanded cooling load, that is, adapt the pumping capacity as much as according the demand in real time. Thus reducing energy consumption, thus contributing to being a sustainable and environmentally friendly company.